HUBUNGAN LINGKUNGAN BELAJAR DAN MOTIVASI BELAJAR DENGAN MINAT BELAJAR MAHASISWA SEMESTER III PROGRAM STUDI DIPLOMA III KEBIDANAN STIKES PRIMA NUSANTARA BUKITTINGGI - Nova Asvio (IAIN Batusangkar, 2016)
This research was started from the students’ interest in STIKes Prima Nusantara Bukittinggi Diploma III of midwifery in the academic year 2011 on learning were high. There were 91,9% of students got achievement index > 2,75. This research was aimed at finding the correlation of learning environment, students’ learning motivation and students’ learning interest. This research belongs to survey analitic by using cross sectional approach. The samples were 96 students and the questionnaire was used as instrument. The data analysis were done by applying statistical test chi square (x2). The findings revealed that there were meaningful correlations of learning environment, students’ learning motivation and students’ learning interest. Keywords: Learning Environment, Students’ Learning Motivation and Students’ Learning Interest